SPSS FOR PARAMETRIC STATISTICS - Maizam Alias; Wan Azlinda Wan Mohamed; Lai Chee Sern; Alias Masek; Ridzwan Che Rus (2020)
The book is written for students, educators and researchers who are beginners to using the Statistical Package for the Social Sciences (SPSS). It consists of six topics on parametric statistical analysis methods and procedures that are often used in the education and social science practice and research. The book starts off with the t-test which is a familiar inferential statistical analysis method to many in the social science discipline.Each topic is dedicated to one particular statictical method only which makes the book an easy reference to use. A topic begins with a brief description of a specific method; what it is, and where it is to be applied, followed by an example on the procedure to use using SPSS, and ends with a set of questions for enhancing a reader’s statistical analysis skills using SPSS.A unique feature of this book which is not often found in other statistics book is that, it gives an explanation on how a test result can be professionally reported using a well known format, i.e. the American Psychological Association format (APA). Knowing how to report results properly helps in improving the quality of a report, thesis or a research paper.